Heterogeneous resource cooperative game in space-ground computing power network - Yutong ZHANG; Yuming PENG; Boya DI; Lingyang SONG (Tongxin xuebao)
To deal with the resource competition among satellites in the multi-satellite space-ground computing network, a space-ground heterogeneous resource cooperative game mechanism was designed in terms of the computing and spectrum domains.Each satellite published a computing task which was independent of other tasks and relied on UE to generate raw data.By competing the resources of user terminals and UE, the task offloading and processing was achieved.To provide real-time data services, a distributed scheme was proposed based on multi-agent reinforcement learning to coordinate the computing and spectrum resource competition among satellites, thereby minimizing the system latency.Simulation results indicated that, compared with the existing schemes, the proposed algorithm achieves a lower system latency by fully utilizing the computing and spectrum resources and coordinating the resource competition.